2016
DOI: 10.1088/0022-3727/49/26/265003
|View full text |Cite
|
Sign up to set email alerts
|

Large difference between the magnetic properties of Ba and Ti co-doped BiFeO3bulk materials and their corresponding nanoparticles prepared by ultrasonication

Abstract: The ceramic pellets of the nominal compositions Bi0.7Ba0.3Fe1−xTixO3 (x = 0.00-0.20) were prepared initially by standard solid state reaction technique. The pellets were then ground into micrometer-sized powders and mixed with isopropanol in an ultrasonic bath to prepare nanoparticles. The X-ray diffraction patterns demonstrate the presence of a significant number of impurity phases in bulk powder materials. Interestingly, these secondary phases were completely removed due to the sonication of these bulk powde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…We have calculated the remanent magnetization (M r ) of the synthesized samples from the M-H hysteresis loops. 49,50 The maximum magnetization (M s ) at an applied magnetic eld of 13 kOe is also calculated from the hysteresis loops. Both M r and M s are higher for BFO nanoparticles prepared at 160 C hydrothermal reaction temperature.…”
Section: Magnetic Characterizationmentioning
confidence: 99%
“…We have calculated the remanent magnetization (M r ) of the synthesized samples from the M-H hysteresis loops. 49,50 The maximum magnetization (M s ) at an applied magnetic eld of 13 kOe is also calculated from the hysteresis loops. Both M r and M s are higher for BFO nanoparticles prepared at 160 C hydrothermal reaction temperature.…”
Section: Magnetic Characterizationmentioning
confidence: 99%
“…Recently, much attention has been paid to understand the effect of chemical composition [13][14][15][16], pressure [17,18], temperature of the synthesis, and annealing [19,20] on crystal structure and physical properties of BFO-based nanopowders. A number of studies reported strong dependence of BFO electromagnetic properties from its nanoscale structure [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have also been observed for other BFO-related materials. 26,56,57 For instance, the M(H) loops measured up to 60 kOe (6 T) for Sm/Nb-codoped BFO 56 or up to 9 T for Ca/Mncodoped BFO 58 could not reach magnetization saturation. On the other hand, Wang et al recently found that, with codoping of rare-earth and metal elements at Bi and Fe sites, respectively, the center of the M(H) loops became larger, weak ferromagnetism could be observed, and the magnetization increased substantially, indicating a transformation from an AFM to FM state.…”
Section: Resultsmentioning
confidence: 99%
“…The EB effect has also been observed in many other BFO-related materials with low-field M(H) loops. 57,59 The EB effect in the Bi 0.5 La 0.5 Fe 1Àx Cr x O 3Àd compounds originates from unidirectional exchange anisotropy due to the exchange coupling at interfaces between FM and AFM domains. It is worth noting that presence of long-range FM order was not detected by the NPD measurements, implying a short-range character of the FM phase in the samples.…”
Section: Resultsmentioning
confidence: 99%